2019
DOI: 10.4103/jomfp.jomfp_309_18
|View full text |Cite
|
Sign up to set email alerts
|

Familial Vitamin D-dependent rickets Type 2A: A report of two cases with alopecia and oral manifestations

Abstract: Rickets is a metabolic bone disease that develops as a result of inadequate mineralization of growing bone due to disruption of calcium, phosphorus and/or Vitamin D metabolism. In addition, several rare genetic causes of rickets have also been described, which can be divided into two groups. The first group consists of genetic disorders of Vitamin D biosynthesis and action, such as Vitamin D-dependent rickets Type 1A, Type 1B, Type 2A (VDDR2A) and Type 2B. The second group involves genetic disorders of excessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In the present study, a case of a supernumerary tooth was observed in an 8-year-old boy, which coincides with a case described by Thakur. 43 Regarding dental caries, this was the pathology with the highest frequency, similar to what has been reported in other studies, such as the one conducted by Rabbani et al 23…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, a case of a supernumerary tooth was observed in an 8-year-old boy, which coincides with a case described by Thakur. 43 Regarding dental caries, this was the pathology with the highest frequency, similar to what has been reported in other studies, such as the one conducted by Rabbani et al 23…”
Section: Discussionsupporting
confidence: 83%
“…4 Additionally, genetic causes of rickets (hereditary rickets) are rare, accounting for about 13% of total rickets. 5 The comprehensive nutrition survey, by ministry of health and family welfare (GOI), states that the prevalence of vitamin D deficiency as defined by adolescents' level of 25OHD <12 ng/ml, has been found to be 14% among children aged 1-4 years ,18% among school aged children (5-9 years) and 24% among adolescent. 6 As there is a high prevalence of nutritional rickets, another aetiology of rickets is not frequently thought of.…”
Section: Discussionmentioning
confidence: 99%
“…1,12 Prithi et al, Thakur et al, Azemi et al and Aunuwar et al and our case has alopecia. 3,5,10,12 Few of the authors reported regarding enamel hypoplasia. Prithi et al and Thakur have reported about enamel hypoplasia as mentioned in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations